PENGARUH PENGGUNAAN E-LEARNING TERHADAP HASIL BELAJAR DENGAN MINAT BELAJAR DAN MOTIVASI SEBAGAI VARIABEL INTERVENING - Reni Agistiningsih; Elly Astuti; Farida Styaningrum (STKIP Singkawang, 2023)
This study aims to explain the Effect of E-Learning Use on Learning Outcomes with Interest in Learning and Motivation as intervening variables. The background of this research is how students respond to and carry out learning with current conditions, namely the Covid-19 pandemic and Industrial Work Practices which must be carried out simultaneously to continue to support learning achievement. Then the suitability of alternatives that suit these needs by conducting Online learning or Electronic Learning (E-Learning). The subject carried out by the researcher was student X. Data analysis techniques using SmartPLS, with quantitative methods. Questionnaire and documentation data collection techniques with a total sample of 70 students. The study results can be concluded that using E-Learning, interest in learning, and motivation positively affect learning outcomes. Interest in learning has a positive effect on motivation. E-Learning use positively affects learning outcomes through an interest in learning and motivation as variables that can inventory research variables